Diagnostic Accuracy of Transvaginal Ultrasound for Tubal Ectopic Pregnancy Using Laparotomy as the Gold Standard - Mehwish Zeb; Kousar Robeen; Noreen Khattak; Sajida Riaz (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To evaluate the diagnostic accuracy of transvaginal Ultrasound (TVUS) in detecting tubal ectopic pregnancies compared to laparotomy, which is considered the gold standard for diagnosis METHODOLOGY: This study employed a cross-sectional design and was conducted within the Obstetrics and Gynaecology Department of Khyber Teaching Hospital, Peshawar, from February to August 2017. A total of 223 women aged 15 to 45 years were included in the study. Consecutive patients suspected of having an ectopic pregnancy were enrolled. All participants underwent transvaginal Ultrasound (TVUS), followed by laparotomy for the definitive diagnosis of ectopic pregnancy. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of TVUS were calculated based on the comparison with laparotomy findings. Data analysis was performed using SPSS version 22. RESULTS: The average age of the participants was 29.8 years (SD ± 6.8). Transvaginal Ultrasound detected ectopic pregnancy in 60.1% of patients, while laparotomy identified ectopic pregnancies in 50.2% of patients. The diagnostic accuracy of TVUS was calculated as follows: sensitivity: 90.1%, specificity: 70.3%, positive predictive value (PPV): 75.4%, negative predictive value (NPV): 87.6% CONCLUSION: Transvaginal Ultrasound, a widely recognized diagnostic tool for ectopic pregnancy, demonstrates high sensitivity and specificity when compared to laparotomy as the gold standard. It serves as an essential radiological tool for the early and accurate diagnosis of tubal ectopic pregnancy, supporting timely clinical decision-making and management.